The Role of Islamic Work Culture In Moderating The Influence of Overtime Work, Empowerment, And Procrastination on Employee Performance - Setyaningrum, Dwi; Saifudin, Saifudin (Al-Muraqabah: Journal of Management and Sharia Business, 2024)
Human Resources are the most important aspect for a company, because this is where sustainable production must be achieved.  The success or failure of a company in achieving its goals is determined by the professional level and ability of its employees in completing the tasks given by their superiors.  Human resources have a function as a driving force, maintaining the success of a business and controlling it.  The approach in this research uses quantitative and data collection by distributing questionnaires.  The population in this study were all PT AML. The sample used was 309 respondents.  The sampling technique uses a saturated sampling technique.  The data analysis technique uses multiple linear regression analysis with the help of SPSS for Windows version 22 software. The conclusions of this research are (1) Working overtime, empowerment, and procrastination influence employee performance.  (2) Islamic work culture is able to moderate the influence of working overtime, empowerment and procrastination on employee performance at PT. AML